The Impact of Functional Food on the Intestinal Microbiota in Relation to Chronic Noncommunicable Diseases - Rosângela dos Santos Ferreira; Rita de Cássia Avellaneda Guimarães; Ligia Aurélio Bezerra Maranhão Mendonça; Priscila Aiko Hiane (Annals of Pancreatic Disorders and Treatment - Peertechz Publications, 2017)
The World Health Organization (WHO) states that obesity is characterized as a positive energy balance that favors the accumulation of fat, associated with metabolic complications related to health risks such as high cholesterol and triglyceride levels, high blood pressure, and resistance to insulin [1]. These obesity-related alterations, such as high systemic blood pressure, dyslipidemia, high fasting glycemia, and central obesity, are the main characteristics of Metabolic Syndrome (MS), according to the International Diabetes Federation. MS is defined as the combination of physiological, biochemical, clinical, and metabolic factors associated with increased cardiovascular risk and the risk of type II diabetes mellitus [2].